Description Of Characteristics Of Pulmonary Tuberculosis Patients At The Pulmonary Poly Adam Malik Hospital Medan 2020 - Nasipta Ginting; Meldawati Sitanggang (Science Midwifery, 2021)
Background: Tuberculosis is a disease caused by Mycobacterium tuberculosis. Tuberculosis usually attacks the lungs, which can then attack all parts of the body. WHO in 2017 reported that there were 1.3 million deaths caused by pulmonary tuberculosis and there were 300,000 deaths due to pulmonary tuberculosis. Indonesia is a country with the third rank after India and China in cases of pulmonary tuberculosis. In 2017, the Case Notification Rate/CNR (new cases) number of pulmonary tuberculosis AFB (+) in North Sumatra was 104.3 per 100,000. Purpose: to identify the characteristics of pulmonary tuberculosis patients based on age, gender, education, and occupation. Methods: This type of research is a descriptive study using a total sampling technique of 525 patients. Data analysis using univariate analysis. Results: in terms of age the most at the age of 41-60 years, namely 204 patients (39%), the most gender was male, namely 344 patients (65.5%), the most education was in high school, namely 418 patients (80%) , and the highest number of occupations is self-employed, namely 160 people (31%). Conclusion: the results of this study indicate that based on the characteristics of patients with pulmonary tuberculosis who suffer the most, namely high school education. Suggestion: it is hoped that the hospital will further improve health education to the community, especially for patients with pulmonary tuberculosis